STRES KERJA GURU PEREMPUAN DI KECAMATAN KASIHAN BANTUL YOGYAKARTA - Akif Khilmiyah (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2012)
The purpose of this study was to reveal the working stress of female teachers in Kasihan Bantul Yogyakarta. The research type was qualitative descriptive research with phenomenological paradigm, ethnographic model, and cultural-psychological approach. The research method was depth interview. The research subjects were female married teachers who had children and experienced work-ing stress. The results: first, the women became teachers because of self-actual-ization, socialization, income and happiness. Second, the forms of stress; physical and psychological. Third, cause of stress; (1) simultaneous tasks of home and office, (2) strict discipline, (3) career demand, (4) picking up the child, (5) having a baby, (6) authoritarian boss, (7) uncomfortable office environment, (8) job position promotion. Fourth, gender inequality factors: (1) double burden, (2) being degraded (3) irrational assumption to female teachers, (4) psychological violence or verbal abuse (5) marginalization. Fifth, solution: (1) mutual respect (2) patient, open, responsible, caring, or avoidance of closeness to the hard and painful character, (3) still working in mild pain and just confiding to close friend, but asking permission when having ill, (5) making a priority job.